Assessing the Market Readiness for Medical Cannabis in Greece: A Qualitative Study of Patient Perspectives - Christos Ntais; Yioula Melanthiou (Medicines)
Background: The introduction of medical cannabis in Greece marks a shift in healthcare policy, yet patient attitudes remain underexplored. Methods: This qualitative study examines the market readiness for medical cannabis through semi-structured interviews with 24 participants—12 users of cannabidiol (CBD)-based formulations and 12 medical cannabis-naive individuals. Results: CBD-experienced patients generally perceive cannabis-based treatments as beneficial for managing musculoskeletal pain, migraines, anxiety, stress and sleep disturbances, despite concerns over product quality, cost and limited medical guidance. Medical cannabis-naive participants express skepticism due to stigma and perceived insufficient evidence but acknowledge potential therapeutic value within a regulated framework. This study highlights the need for better patient education, physician training and clear regulatory guidelines to support responsible market entry. Conclusions: These findings offer important insights for policymakers, healthcare providers and the pharmaceutical industry, emphasizing the need for a structured, evidence-based approach to medical cannabis integration in Greece. Further research is needed to assess long-term patient experiences and the evolving impact of regulatory changes on market dynamics.